2015
DOI: 10.1161/circulationaha.115.016261
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Microbleeds Are Associated With an Increased Risk of Stroke

Abstract: 509S troke is the second leading cause of death worldwide and the third most common cause of disability-adjusted lifeyears.1,2 Although stroke has an acute onset, there is abundant evidence for a long subclinical period in which cerebrovascular pathology accumulates and can be visualized on noninvasive brain imaging. Markers of subclinical cerebrovascular pathology that are known to increase the risk of ischemic stroke are white matter lesions and lacunes. 3 In the past decade, punctuate hemorrhagic lesions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(176 citation statements)
references
References 31 publications
8
165
3
Order By: Relevance
“…160 In that study, there were overall more ischemic strokes than hemorrhagic strokes in the individuals with microbleeds. The increased risks were independent of silent brain infarcts and WMHs.…”
Section: Anticoagulation and Other Medical Therapies In Patients Withmentioning
confidence: 80%
“…160 In that study, there were overall more ischemic strokes than hemorrhagic strokes in the individuals with microbleeds. The increased risks were independent of silent brain infarcts and WMHs.…”
Section: Anticoagulation and Other Medical Therapies In Patients Withmentioning
confidence: 80%
“…Other studies have found that the presence of CMB, and especially multiple CMB, was associated with an increased risk of stroke, including first-ever ischemic stroke. 23,24 Presumably, the follow-up period in our study period was too short to detect an increase in stroke recurrence. Likewise, our …”
Section: Discussionmentioning
confidence: 91%
“…Multiple diseases, including traumatic brain injury (TBI) 1, 2 , stroke 3, 4 , hypertension and cerebral amyloid angiopathy (CAA) 5 require assessment of cerebral microhemorrhage (CMH) for diagnosis and / or management. However, the choice of neuroimaging technique can provide very different assessments of CMH burden.…”
Section: Introductionmentioning
confidence: 99%